ANALISIS PENGENDALIAN MANAJEMEN INTERNAL TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI PADA BANK UMUM PEMERINTAH DI WILAYAH BANDA ACEH - Faridah Iriani; Yushita Marini (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
This study aims to analyze the performance of the internal management control to the system accounting information on a government-owned bank in the city of Banda Aceh. The study was conducted in three state-owned commercial banks in the city of Banda Aceh, namely Rakyat Indonesia’s Bank, Negara Indonesia’s Bank and Tabungan Negara’s Bank. Data was collected by means of documentation, interviews and questionnaires. After testing the quality of the data and then the data were analyzed using qualitative descriptive analysis of statistical data. The survey results revealed internal management control in state-owned commercial bank in the city of Banda Aceh was good enough, thereby increasing the efficiency and effectiveness of the acquisition of information. Accounting information system performance is affected by the internal management controls were nice, user involvement in system development, education and training on accounting information systems and also the presence of prominent representatives are actively involved in the information system.